2010
DOI: 10.1099/mic.0.038331-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of vimA in cell surface biogenesis in Porphyromonas gingivalis

Abstract: The Porphyromonas gingivalis vimA gene has been previously shown to play a significant role in the biogenesis of gingipains. Further, in P. gingivalis FLL92, a vimA-defective mutant, there was increased auto-aggregation, suggesting alteration in membrane surface proteins. In order to determine the role of the VimA protein in cell surface biogenesis, the surface morphology of P. gingivalis FLL92 was further characterized. Transmission electron microscopy demonstrated abundant fimbrial appendages and a less well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 88 publications
2
46
0
1
Order By: Relevance
“…Our data do not distinguish, however, whether the low activity in the medium was due to lack of secretion of the gingipains or whether the proteins are secreted in an inactive form. In addition, a W83 strain with a mutation in VimA has been reported to express a fimbrial protein with reactivity to anti-FimA antibody that is not present in wild-type P. gingivalis W83 (36). We were unable to detect an anti-FimA reactive band in either the parent strain or the ⌬77bpIR mutant (data not shown), indicating that the 77bpIR region does not modulate expression of this protein.…”
Section: Resultsmentioning
confidence: 38%
“…Our data do not distinguish, however, whether the low activity in the medium was due to lack of secretion of the gingipains or whether the proteins are secreted in an inactive form. In addition, a W83 strain with a mutation in VimA has been reported to express a fimbrial protein with reactivity to anti-FimA antibody that is not present in wild-type P. gingivalis W83 (36). We were unable to detect an anti-FimA reactive band in either the parent strain or the ⌬77bpIR mutant (data not shown), indicating that the 77bpIR region does not modulate expression of this protein.…”
Section: Resultsmentioning
confidence: 38%
“…The activation of these gingipains is associated with several genes, including vimA, vimE, and vimF, that modulate the posttranslational glycosylation of those proteins (44,(62)(63)(64). These genes are part of the 6. locus which has previously been shown to be important to the pathogenic potential of P. gingivalis (1,26,44,(62)(63)(64).We have demonstrated that the bcp and recA genes play the expected role in oxidative stress resistance and DNA repair, respectively (26). The association of these genes with the vim genes on the same transcriptional unit could be considered an important strategy for P. gingivalis to coordinate its oxidative stress and proteolytic activities.…”
mentioning
confidence: 99%
“…The major proteases, called gingipains, consist of arginine-specific (Arg-gingipain [Rgp]) and lysine-specific (Lysgingipain [Kgp]) proteases that are both extracellular and cell membrane associated (32). The activation of these gingipains is associated with several genes, including vimA, vimE, and vimF, that modulate the posttranslational glycosylation of those proteins (44,(62)(63)(64). These genes are part of the 6. locus which has previously been shown to be important to the pathogenic potential of P. gingivalis (1,26,44,(62)(63)(64).…”
mentioning
confidence: 99%
“…In this issue, Osbourne et al (2010) show that the VimA protein can control capsular biogenesis and fimbrial synthesis. A vimA mutant strain displayed an irregular polysaccharide capsule and more fimbriae compared with the parental strain.…”
Section: Controlling Porphyromonas Gingivalis Requires Vimmentioning
confidence: 99%
“…Further study of VimA will undoubtedly reveal more important circuitry. It is also worthy of note that Osbourne et al (2010) showed that the VimA mutant is more sensitive to globomycin and vancomycin, making VimA function a potential target for…”
mentioning
confidence: 99%